2014
DOI: 10.1002/ccd.25467
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing radiation dose reporting in the pediatric cardiac catheterization laboratory—A multicenter study by the CCISC (Congenital Cardiovascular Interventional Study Consortium)

Abstract: PKA /BW appeared to be the most reliable standard to report radiation dose across all procedure types and patient age. We recommend PKA /BW to be used as the standard unit in documenting radiation usage in pediatric laboratories and can be used to evaluate strategies to lower radiation dosage in pediatric patients undergoing cardiac catheterizations. © 2014 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 13 publications
4
40
2
9
Order By: Relevance
“…Secondly, a lack of correlation should not imply that there is no relationship between variables-a U-shaped relationship yields a correlation coefficient of zero. While the setting of reference doses specific to individual procedure types by Kobayashi et al 18 should be applauded, our data do not support the recommendation that P KA /kg should be used as the standardized measure of radiation doses, at least not in isolation.…”
Section: 4contrasting
confidence: 49%
See 1 more Smart Citation
“…Secondly, a lack of correlation should not imply that there is no relationship between variables-a U-shaped relationship yields a correlation coefficient of zero. While the setting of reference doses specific to individual procedure types by Kobayashi et al 18 should be applauded, our data do not support the recommendation that P KA /kg should be used as the standardized measure of radiation doses, at least not in isolation.…”
Section: 4contrasting
confidence: 49%
“…The potential for relatively high radiation doses raises concerns of the long-term risk of developing cancer. [1][2][3] The radiation doses and associated risks from cardiac catheterizations in children and young people have recently received considerable attention, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] although relatively fewer data on doses in the UK have been published. 7,17,22,23 Most previous assessments have been based on kerma area product (P KA , also known as dose-area product), defined as collision air kerma integrated over beam area.…”
mentioning
confidence: 99%
“…They recommended that the kerma area product divided by body weight should be used as a standard reporting unit for pediatric cardiac catherization. 51 …”
Section: Iden Fica Onmentioning
confidence: 97%
“…Recently, there have been data reported that suggest radiation dose correlates with body weight better than with age in the pediatric population, and thus radiation dose by body weight (mGy cm 2 /kg or lGy m 2 /kg) is the most reliable standard to report radiation dose across all procedure types and ages. This method of reporting has recently been suggested by the Congenital Cardiovascular Interventional Study Consortium [14]. Thus, we have chosen to report dose-area product normalized to weight (mGy cm 2 /kg) as well as There is narrowing of the midcircumflex artery (solid arrow) and distal LAD (box arrow) visualized in multiple viewing planes.…”
Section: Data Collectionmentioning
confidence: 99%